Spatiotemporal phosphoprotein distribution and associated cytokine response of a traumatic injury. (March 2016) - Han, Alice A.; Currie, Holly N.; Loos, Matthew S.; Vrana, Julie A.; Fabyanic, Emily B.; Prediger, Maren S.; Boyd, Jonathan W.
Highlights: Spatiotemporal gradient of phosphoproteins is observed following a traumatic injury. Phosphorylation is correlated to cytokine production following a traumatic injury. Correlations between protein and cytokine suggest coordinated signaling after injury. Abstract: Molecular mechanisms of wound healing have been extensively characterized, providing a better understanding of the processes involved in wound repair and offering advances in treatment methods. Both spatial and temporal investigations of injury biomarkers have helped to pinpoint significant time points and locations during the recovery process, which may be vital in managing the injury and making the appropriate diagnosis. This study addresses spatial and temporal differences of phosphoproteins found in skeletal muscle tissue following a traumatic femur fracture, which were further compared to co-localized cytokine responses. In particular, several proteins (Akt, ERK, c-Jun, CREB, JNK, MEK1, and p38) and post-translational phosphorylations (p-Akt, p-c-Jun, p-CREB, p-ERK1/2, p-MEK1, p-p38, p-GSK3α/β, p-HSP27, p-p70S6K, and p-STAT3) associated with inflammation, new tissue formation, and remodeling were found to exhibit significant spatial and temporal differences in response to the traumatic injury. Quadratic discriminant analysis of all measured responses, including cytokine concentrations from previously published findings, was used to classify temporal and spatial observations at high predictive rates, further confirming that distinct spatiotemporal distributions for total protein, phosphorylation signaling, and cytokine (IL-1α, IL-1ß, IL2, IL6, TNF-α, and MIP-1α) responses exist. Finally, phosphoprotein measurements were found to be significantly correlated to cytokine concentrations, suggesting coordinated intracellular and extracellular activity during crucial periods of repair. This study represents a first attempt to monitor and assess integrated changes in extracellular and intracellular signaling in response to a traumatic injury in muscle tissues, which may provide a framework for future research to improve both our understanding of wounds and their treatment options.